Understanding EFL Teacher Engagement in TDTs’ Collaborative Curriculum Design: A Chinese Case Study From the Activity Theory Perspective - Wu, Zhonghua; Li, Jian; Cheng, Le (Frontiers in Psychology, 2022)
While collaborative curriculum design (CCD) has gained increasing attention in the field of education, there is scant research as to how EFL teachers implement it in authentic design contexts. The present case study places particular emphasis on teacher activities during collaborative EFL curriculum development in China. The researchers adopt Activity Theory as an analytical tool to understand the relationships between EFL teachers, reform goals, and various aspects of the sociocultural context in which CCD is advocated, highlighting the pivotal role that mediation of knowledge/experience plays in the teacher learning community. Research findings indicate that the TDTs’ collaborative process is a socially constructed and culturally mediated activity that promotes EFL teacher development. Moreover, in-service teachers are prone to take challenges through educational reforms out of teacher motives and external stimuli. Limitations of the CCD model are also discussed to shed light on future research.